1991
DOI: 10.3758/bf03197868
|View full text |Cite
|
Sign up to set email alerts
|

The effects of varying the interreinforcement interval on appetitive contextual conditioning

Abstract: Appetitive contextual conditioning in rats and ringdoves was investigated in six experiments. In Experiment 1, differential contextual training produced greater anticipatory activity in rats in the presence of a context paired with food than it did in rats in the presence of a different context in which food was never presented. Furthermore, the rats showed a preference for the context associated with food when they were given a simultaneous choice test between contexts. In Experiment 2, rats were more active … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 41 publications
0
16
0
2
Order By: Relevance
“…For example, some authors (e.g., Mustaca, Gabelli, Papini, & Balsam, 1991) have suggested that shorter ITIs and, hence, higher rates of US presentation encourage greater context conditioning, which might in turn influence the effectiveness of various trial types in generating discrimination learning or performance. In opposite significance (e.g., Grant, 1975;Hogan et al, 1981;Pontecorvo, 1983) or generated a response that was incorrect for the present trial (e.g., Roitb1at & Scopatz, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…For example, some authors (e.g., Mustaca, Gabelli, Papini, & Balsam, 1991) have suggested that shorter ITIs and, hence, higher rates of US presentation encourage greater context conditioning, which might in turn influence the effectiveness of various trial types in generating discrimination learning or performance. In opposite significance (e.g., Grant, 1975;Hogan et al, 1981;Pontecorvo, 1983) or generated a response that was incorrect for the present trial (e.g., Roitb1at & Scopatz, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…First, if a light comes on and remains on for a long time before the grain, the bird does not peck at it. Instead the bird becomes hyperactive and paces back and forth in the chamber(Mustaca, Gabelli et al 1991; Silva and Timberlake 2005). Thus a long CS does not result in a failure of learning; the learning is intact, but the way it is expressed changes based on the duration of the CS (see also(Holland 1980)).…”
Section: 2 Temporal Information and The Modulation Of Behaviormentioning
confidence: 99%
“…From this perspective, the conditioning paradigm may be construed as consisting of several extended "simultaneous" conditioning trials in which illumination and turbulence overlap (albeit their onsets were delayed by 7-8 sec). Although Talk et al justified their use of short US interstimulus intervals (ISIs) on the basis of findings with vertebrates that contextual conditioning is facilitated for massed versus distributed USs, the USs used in those studies (electric shock in Williams, Frame, & LoLordo, 1991; small rat chow pellets that were immediately consumed or 4-sec pigeon grain presentations in Mustaca, Gabelli, Papini, & Balsam, 1991) were brief and probably lasted little longer than their nominal presentation durations.…”
Section: Additional Reports Of Contextual Conditioning In Hermissendamentioning
confidence: 99%